2016
DOI: 10.5152/iao.2016.1612
|View full text |Cite
|
Sign up to set email alerts
|

Potential Curative Role of Hypericum Perforatum in an Experimental Rat Model of Tympanic Membrane Perforation

Abstract: OBJECTIVE:Our aim was to investigate the curative role of topical Hypericum perforatum (HP) in a rat model of tympanic membrane perforation in a histopathological manner. MATERIALS AND METHODS:This study was conducted on 30 female Sprague-Dawley rats. An HP extract was prepared as a suspension in pure olive oil. In all rats, the right and left tympanic membranes were perforated by a fine puncture under a microscope. Rats were randomly assigned to three groups. The HP extract was given as drops on a daily basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…It was shown that the systemic effect of the oily solution of HP is similar to that of its topical form. However, only the topical form of HP was used in the study by Yaşar et al [3] , in which the number of leucocyte, neovascularization, and fibroblasts, which are the findings of acute inflammation, was higher than that in previous studies in which anti-inflammatory effects of HP were shown [3] .…”
Section: Dear Editormentioning
confidence: 97%
See 2 more Smart Citations
“…It was shown that the systemic effect of the oily solution of HP is similar to that of its topical form. However, only the topical form of HP was used in the study by Yaşar et al [3] , in which the number of leucocyte, neovascularization, and fibroblasts, which are the findings of acute inflammation, was higher than that in previous studies in which anti-inflammatory effects of HP were shown [3] .…”
Section: Dear Editormentioning
confidence: 97%
“…They reported that an increase in leukocyte counts enables matrix metalloproteinases to promote re-epithelization and remodeling and that an increase in fibroblasts promotes collagen synthesis and wound healing. They also indicated that their study on the potential curative role of HP in the healing of TM perforation was the first in the literature [3] . However, in the study by Eğilmez et al [4] published in July 2015, the effect of HP on myringosclerosis and the healing of TM perforations in all animals was evaluated, and it was also found that the rate of myringosclerosis in the lamina proprias of TMs is lower because of the high anti-inflammatory activity of HP.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Arnica montana reduces pain, has anti-inflammatory effects and potentiates tissue repair [29,30]. Hypericum perforatum provides anti-inflammatory effect and drives tissue regeneration and scarring [31][32][33][34]. Calendula officinalis reduces swelling and distension, boosts healing of mild injuries and prevents infection [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Laceration of rodent tympanic membranes leads to regular spontaneous closure within weeks [ 34 , 35 , 36 , 37 ]. Therefore, various methods of mechanical and biochemical attenuation of spontaneous closure have been reported (e.g., thermal myringotomies, epithelialized flaps, and topical mitomycin/corticoid) [ 3 , 18 , 32 , 38 , 39 , 40 , 41 , 42 ]. Still, the resulting defect size is not standardized, and wound attenuation may interfere with wound treatment.…”
Section: Introductionmentioning
confidence: 99%